Developing and piloting a self-assessment tool for medication review competence of practicing pharmacists based on nationally set competence criteria - Noora Lias (BMC, 2021)
Abstract Background New competence requirements have emerged for pharmacists as a result of changing societal needs towards more patient-centred practices. Today, medication review competence can be considered as basic pharmaceutical competence. Medication review specific competence criteria and tools for self-assessing the competence are essential in building competences and a shared understanding of medication reviews as a collaborative practice. The aim of this study was to develop and pilot a self-assessment tool for medication review competence among practicing pharmacists in Finland. Methods The development of the self-assessment tool was based on the national medication review competence criteria for pharmacists established in Finland in 2017 and piloting the tool among practicing pharmacists in a national online survey in October 2018. The pharmacists self-assessed their medication review competence with a five-point Likert scale ranging from 1 for “very poor/not at all” to 5 for “very good”. Results The internal consistency of the self-assessment tool was high as the range of the competence areas’ Cronbach’s alpha was 0.953–0.973. The competence areas consisted of prescription review competence (20 items, Cronbach’s alpha 0.953), additional statements for medication review competence (11 additional items, Cronbach’s alpha 0.963) and medication review as a whole, including both the statements of prescription review and medication review competence (31 items, Cronbach’s alpha 0.973). Competence items closely related to routine dispensing were most commonly self-estimated to be mastered by the practicing pharmacists who responded (n = 344), while the more clinical and patient-centred competence items had the lowest self-estimates. This indicates that the self-assessment tool works logically and differentiates pharmacists according to competence. The self-assessed medication review competence was at a very good or good level among more than half (55%) of the respondents (n = 344). Conclusion A self-assessment tool for medication review competence was developed and validated. The piloted self-assessment tool can be used for regular evaluation of practicing pharmacists’ medication review competence which is becoming an increasingly important basis for their contribution to patient care and society.